Technology Design to Improve Plant Quality with IoT-Based Plant Temperature and Humidity Monitoring System - Ganang Aris Setiawan; Joko Hariyono; Agus Ramelan (Journal of Electrical, Electronic, Information, and Communication Technology, 2022)
This project focuses on the issue of improving the quality of plants, especially lettuce. Lettuce grows best in a temperature range of 25°C to 28°C and a humidity range of 65% to 78%. In order to grow high quality lettuce, it is necessary to adjust the temperature and humidity. But when you don't have time to pay attention to these details for other important work, that becomes a problem. To solve this problem, we use the Internet of Things to monitor assets anytime, anywhere. We made it possible. Also, this monitoring system saves a lot of time. I use an instant messenger called Telegram. Telegram Messenger is an open source, free, cross-platform application. Use API Bot in Telegram to create intelligent bots that react to messages about surveillance. The DHT11 Temperature and Humidity Sensor is used to provide sensor temperature and humidity readings. The Arduino Integrated Development Environment (IDE) software is used to create the source code, and the ESP 12e acts as the brains of the technology we develop and can connect to the internet. The results of this temperature and humidity monitoring can be accessed by typing commands into the Telegram bot. Statistics and other visual data can also be monitored from websites developed by us.